Zig-Zag Running Training's Impact on Dribbling Speed - Veni Suryani; Dessy Wardiah; Siti Ayu Risma Putri; Putri Cicilia Kristina; Sugarwanto Sugarwanto (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The primary objective of this study is to investigate the potential impact of zig-zag running training on the dribbling speed of basketball extracurricular students enrolled at SMP Negeri 1 Bunga Mayang OKU Timur. The study aims to analyze whether this particular training technique can improve the students' dribbling speed, which is a crucial skill in basketball. The study will collect data from a sample of students and analyze the results to conclude the effectiveness of zig-zag running training on dribbling speed. Materials and methods. This is descriptive quantitative research that uses data analysis techniques to measure instruments or tests. The research employs T-test statistical data to conduct normality and hypothesis tests. The research subjects are students participating in basketball extracurricular activities at SMP Negeri 1 Bunga Mayang. Results. According to the analysis of the research data, the value of t_table is 1.860. This value has been obtained from the t distribution with dk (10-2) = 8 and α=0.05, as listed in the table. The hypothesis testing criteria indicate that if t_count > t_table, the Hα hypothesis is accepted, and if Ho t_count < t_tabel, it is rejected. The t_count value in this case is 14.09, which is greater than the t_table value of 1.860. Therefore, we can conclude that there is a significant difference between the pre-test and post-test. Conclusion. After conducting the necessary tests and analysis, it has been found that the Ho hypothesis, which stated that there is no significant influence of zig-zag running training on dribbling speed in basketball extracurricular students at SMP Negeri 1 Bunga Mayang OKU Timur, is not supported by the data. On the other hand, the Hα hypothesis, which states that there is an influence of zig-zag running training on dribbling speed in the same group of students, has been confirmed by the results of the study. Therefore, it can be concluded that the zig-zag running training has a positive impact on the dribbling speed of basketball extracurricular students at SMP Negeri 1 Bunga Mayang OKU Timur.